Minima Cuba : heretical poetics and power in post-Soviet Cuba - Hernández Salván, Marta, 1970- (SUNY series in Latin American and Iberian thought and culture., 2015)
Mnima Cuba analyzes the reconfiguration of aesthetics and power during the Cuban postrevolutionary transition (1989 to 2005, the conclusion of the "Special Period"). It explores the marginal cultural production on the island by the first generation of intellectuals born during the Revolution. The author studies the work of postrevolutionary poets and essayists Antonio Jos Ponte, Rolando Snchez Mejias, and Ivn de la Nuez, among others. In their writing we find the exhaustion of the allegorical and melancholic rhetoric of the Cuban Revolution, and the poetics of irony developed in the current biopolitical era. The book will appeal to anyone interested in contemporary literary and cultural studies, poetics, and film studies in Latin America and the Caribbean.